Japanese in an EMI environment: language practices and identity construction among Chinese international students in Japan - Dang, Siyan (Frontiers in Education, 2026)
In Japan, the internationalization of higher education is often narrowly equated with the universalization of English. However, this perspective overlooks two key realities: the majority of international students in Japan are not native English speakers, and both faculty and students often have limited English proficiency. As a result, Japanese—the dominant local language—remains the primary medium of everyday communication. This study adopts a qualitative approach to explore the experiences of Chinese international students, who make up the largest segment of Japan's international student population. Twenty one participants were selected for semi-structured, in-depth interviews. The thematic analysis reveals a three-dimensional cognitive framework shaping participants' attitudes toward Japanese: (1) symbolic perceptions of the language; (2) functional roles it plays in various social contexts; and (3) its hierarchical position within their multilingual repertoire. Simultaneously, they experience tensions of dual cultural belonging while negotiating their evolving identities as educational migrants and potential long-term residents.